Analysis of Texbook Durusul Lughah Al-Arabiyah Volume 1 by Imam Zarkasy and Imam Shubani - Panji Prasetya Utama; Daroini, Slamet (Universitas KH. Mukhtar Syafaat, 2024)
This research aims to analyze the textbook Durusul Lughah Al-Arabiyah Volume 1 by Imam Zarkasy and Imam Syubani. Data collection techniques in this research are observation and data analysis. The steps used in this research are observing textbooks, sorting data, determining data, and analyzing data that has been obtained from observations that have been made. The results showed that the textbook Durusul Lughah Al-Arabiyah Volume 1 by Imam Zarkasy and Imam Syubani has met the criteria in the aspects of language and language skills displayed, such as elements of Qowaid, Muhadatsah and Mufradat. In addition, the book has been balanced which has presented four language skills namely maharah istima (listening), kalam (speaking), qiro'ah (reading) and kitabah (writing).